3D printed hydroxyapatite promotes congruent bone ingrowth in rat load bearing defects. (1st May 2022) - Chakraborty, Juhi; Roy, Subhadeep; Ghosh, Sourabh
Abstract: 3D porous hydroxyapatite (HAP) scaffolds produced by conventional foaming processes have limited control over the scaffold's pore size, geometry, and pore interconnectivity. In addition, random internal pore architecture often results in limited clinical success. Imitating the intricate 3D architecture and the functional dynamics of skeletal deformations is a difficult task, highlighting the necessity for a custom-made, on-demand tissue replacement, for which 3D printing is a potential solution. To combat these problems, here we report the ability of 3D printed HAP scaffolds for in vivo bone regeneration in a rat tibial defect model. Rapid prototyping using the direct-write technique to fabricate 25 mm 2 HAP scaffolds were employed for precise control over geometry (both external and internal) and scaffold chemistry. Bone ingrowth was determined using histomorphometry and a novel micro-computed tomography (micro-CT) image analysis. Substantial bone ingrowth was observed in implants that filled the defect site. Further validating this quantitatively by micro-CT, the Bone mineral density (BMD) of the implant at the defect site was 1024 mgHA ccm −1, which was approximately 61.5% more than the BMD found with the sham control at the defect site. In addition, no evident immunoinflammatory response was observed in the hematoxylin and eosin micrographs. Interestingly, the present study showed a positive correlation with the outcomes obtained in our previous in vitro study. Overall, the results suggest that 3D printed HAP scaffolds developed in this study offer a suitable matrix for rendering patient-specific and defect-specific bone formation and warrant further testing for clinical application.